Diagnosis of Workplace Bullying and its Consequences for Worker Health (Management and Connections Journal, 2024)
In this paper, we aimed to present a model to diagnose the occurrence of the workplace bullying and its consequences for worker health, in a credit union in Brazil. This union was reported to the Brazilian Ministry of Labour. We carried out an exploratory,  quantitative and descriptive study. We applied to all 166 employees the questionnaires NAQ-R (Negative Acts Questionnaire), and an adaptation of the SRQ20 (Self Report Questionnaire-20). We analyzed data by means of univariate and bivariate statistics. The results showed an average of 1.34 negative acts per respondent, highlighting two to four cases of severe bullying. The relationship between workplace bullying and physical and psychological symptoms was confirmed. Therefore, we recommend a model to carry out the diagnosis of workplace bullying in a single organization, by using both questionnaires, combined with data and information about the organization and its work environment.
Keywords: Workplace bullying; workers’ health; Credit Union